Utopia as a Parody of Hope? Some Remarks on the Temporality of Politics - Sowiński, Sławomir (Chrześcijaństwo-Świat-Polityka, 2024)
The text addresses the following question: to what extent is the rhetorical figure of modern political utopia a secular parody of religious hope, and to what extent can religious hope also be seen as a kind of restitution or restoration? The solution to this problem is twofold. On a theoretical level, by referring to the Christian concept of time, the text attempts to present the structure of thinking about social life from the perspective of religious hope against the background of the rhetorical figure of utopia. On a more empirical level (case study), the text refers to the process of reconciliation between Poland and Germany after 1965 and poses the question: to what extent can this process be described in terms of hope and to what extent in terms of utopia? In conclusion, the text proposes to distinguish between the rhetorical figure of utopia in its positive (active) sense and its passive (negative) sense, namely a self-limiting utopia.